The nexus between cyberloafing and employee well-being: role of creativity in the Nigerian service sector - Adacha Felix Kwala; Mary Agoyi (Humanities & Social Sciences Communications)
Abstract In the modern service sector, cyberloafing engaging in non-work-related internet activities during work hours has become increasingly prevalent. Although traditional research has often highlighted its negative impact, emerging studies have suggested potential benefits. This study explored the dual nature of cyberloafing, particularly its influence on employee creativity and well-being, with creativity as the mediating factor. Based on the Job Demands-Resources (JD-R) model and Conservation of Resources (COR) theory, we developed a conceptual framework to investigate these relationships. A cross-sectional survey of 379 employees across four service industries in Nigeria was conducted, and the data were analyzed using Partial Least Squares Structural Equation Modelling (PLS-SEM) via SmartPLS 4.1. Comparative analysis of the original and alternative models revealed that specific cyberloafing behaviors are positively associated with enhanced creativity, which in turn contributes to improved employee well-being. However, the alternative model suggests that well-being may lead to increased creativity with the potential to result in cyberloafing. This highlights the need for balanced organizational policies. These findings challenge the traditional view of cyberloafing, as they suggest that, under certain conditions, it may foster innovation and improve morale. This study provides significant theoretical insights and practical implications, advocating a nuanced approach to cyberloafing within organizational policies and cultures.